Grape Seed Proanthocyanidins Induce Apoptosis and Cell Cycle Arrest of HepG2 Cells Accompanied by Induction of the MAPK Pathway and NAG-1 - Lihua Wang; Jicheng Zhan; Weidong Huang (MDPI AG, 2020)
Hepatocellular carcinoma (HCC) is one of the common malignancies leading to death. Although radiotherapy and chemotherapy have certain effects, their side effects limit their therapeutic effect. Phytochemicals have recently been given more attention as promising resources for cancer chemoprevention or chemotherapy due to their safety. In this study, the effects of grape seed proanthocyanidins (GSPs) on the apoptosis, cell cycle, and mitogen-activated protein kinase (MAPK) pathway-related proteins and non-steroidal anti-inflammatory drug-activated gene-1 (NAG-1) expression of HepG2 cells were investigated. The results showed that GSPs inhibited the viability of HepG2 cells in a time- and dose-dependent manner, induced apoptosis and G2/M phase cell cycle arrest, and regulated cell cycle-related proteins, cyclin B1, cyclin-dependent kinase 1, and p21. GSPs also increased reactive oxygen species production and caspase-3 activity. In addition, GSPs also increased the expression of p-ERK, p-JNK, p-p38 MAPK and NAG-1, and GSPs-induced NAG-1 expression was related to the MAPK pathway-related proteins. These data suggest that GSPs may be promising phytochemicals for HCC chemoprevention or chemotherapy.